Screening for HFpEF in pacemaker patients: Study design and protocol of the PM-HFpEF study - Elisabeth Santos; Rafael Teixeira; João Almeida; Paulo Fonseca; Marco Oliveira; Helena Gonçalves; João Primo; Sílvia Diaz; António Barros; Eduardo Vilela; Francisco Sampaio; Francisca Saraiva; et al. (PLoS ONE, 2026)
Background Heart failure with preserved ejection fraction (HFpEF) is common in older multimorbid patients and is associated with substantial morbidity and mortality. Pacemaker (PM) patients may be particularly vulnerable given the clustering of conventional HFpEF risk factors and the hemodynamic effects of long-term right ventricular pacing. Nevertheless, HFpEF is rarely systematically assessed in device clinics. Objectives To determine the prevalence of HFpEF in a cohort of permanent PM patients using a structured guideline-aligned screening protocol and to characterize their clinical, functional, and pacing-related profiles. Methods PM-HFpEF is a single-center, prospective, cross-sectional study conducted at a tertiary hospital in Portugal. Eligible adults with conventional transvenous pacemakers and right ventricular apical pacing implanted between January 2018 and December 2022 will be invited to attend a one-day screening visit. The protocol includes clinical assessment, N-terminal pro-B-type natriuretic peptide testing, 12-lead electrocardiography, comprehensive transthoracic echocardiography, routine device interrogation, frailty assessment (the Portuguese-validated version of the Edmonton Frail Scale), and health-related quality-of-life evaluation using the 12-item Kansas City Cardiomyopathy Questionnaire. Exercise diastolic stress echocardiography using an upper-limb ergometer will be performed when resting findings are inconclusive. HFpEF will be adjudicated according to the 2021 European Society of Cardiology diagnostic definition. Discussion The PM-HFpEF study is designed to provide robust estimates of HFpEF prevalence within a real-world PM population, together with detailed characterization of their clinical and device-related profiles. This information may help inform future clinical assessment and research strategies for this often-overlooked yet clinically significant group of patients.